THE EFFECT OF PRICE AND QUALITY ON PURCHASING DECISIONS ON UNIQLO PRODUCTS - Ratnaningsih, Rini; Rahmadi, Emiro Meirza; Fajri, Refqi Noor; Rabiatul, Rizdyanti; Sugiana, Neng Susi Susilawati (LPKIA, 2025)
This research explores The Effect of Price and Quality on Purchasing Decisions on Uniqlo Products, aiming to understand how these two critical factors influence consumer choices in the fast fashion retail sector. The study specifically targets Uniqlo, a globally recognized Japanese fashion brand known for its simplicity, functionality, and affordability. The primary objective is to examine how consumers perceive price and quality in their decision- making process when purchasing Uniqlo products in the Indonesian market. A qualitative method was employed, using in-depth interviews with 20 respondents who are active Uniqlo customers. Data collection was conducted through semi-structured interviews to capture detailed insights into consumer experiences, preferences, and motivations. The respondents were selected through purposive sampling to ensure relevance and reliability of the findings. The results reveal that while price remains an important factor, perceived product quality—such as durability, comfort, and design—has a stronger influence on purchasing decisions. Most participants emphasized Uniqlo's consistent quality and value for money, which builds consumer trust and brand loyalty. In addition, promotional pricing and seasonal discounts enhance purchase intentions, especially among young adults. Practically, these findings suggest that Uniqlo should continue to emphasize product quality while strategically managing pricing and promotional campaigns. The uniqueness of this study lies in its qualitative approach, offering rich consumer perspectives rarely captured in previous studies that focused mostly on quantitative data